Single-cell profiling identifies heterogeneity of the immune microenvironment in healthy, primary and lymph node metastatic BC - Liu, Chuyu; Zeng, Feng; Gao, Shanshan; Zhang, Nengying; Cai, Yulan (Frontiers in Immunology, 2025)
IntroductionBreast cancer (BC) prognosis is fundamentally dictated by its pronounced molecular and cellular heterogeneity. While single-cell RNA sequencing (scRNA-seq) has detailed the tumor microenvironment (TME) cellular composition, a critical knowledge gap persists regarding the vascular heterogeneity of tumor endothelial cells (TECs) across different BC subtypes. Current TEC classification remains conventional, obscuring whether subtype-specific TECs possess unique transcriptomic signatures that influence treatment response, particularly to anti-angiogenic therapies. Given the pivotal role of tumor vasculature in proliferation and metastasis, and the existing research bias towards Triple-Negative BC (TNBC), a comprehensive investigation into the complexity of the vascular system is warranted. Furthermore, as lymph node metastasis (LNMT) is a major determinant of cancer mortality, distinguishing the endothelial and immune cell subtypes within LNMT microenvironments from primary tumors is essential for clarifying pathogenesis.MethodsTo address this, we integrated scRNA-seq data from primary BC tumors, ER_LN and healthy tissues, generating a robust dataset of 98,000 cells (~ 12 samples). Employing single-cell transcriptomics, spatial transcriptomics, and immunohistochemistry, we precisely delineated the endothelial cell (EC) heterogeneity within matched tumor and peri-tumoral tissues and scrutinized their intricate interactions with immune populations.ResultsWe identified two previously uncharacterized, tumor-enriched endothelial cell subtypes, designated EC4 and EC5, which demonstrate subtype-specific functional adaptations and prognostic significance. EC4 cells, highly prevalent across BC, are principally characterized by antigen presentation, immune cell recruitment, and pro-inflammatory signaling. Conversely, EC5 cells, also enriched in BC, exhibit robust extracellular matrix (ECM) remodeling and potent tumor angiogenesis. We further characterized the functional divergence of EC4 and EC5 within ER tumors relative to HER2 tumors and ER_LN metastases. Our analysis reveals conserved endothelial programming mechanisms across BC subtypes, coexisting with distinct TME-driven transcriptional adaptations. Importantly, interactome analysis highlighted novel and subtype-specific communications between these novel EC subsets and immune cells, particularly CD8+T cells and macrophages. Experimental validation demonstrates that ECs overexpressing APP can mediate the M2 polarization of macrophages, underscoring diverse immunomodulatory roles for EC subsets across different BC contexts.ConclusionsThese findings offer critical and granular insights into the complex interplay between novel EC subtypes and the immune microenvironment in BC progression and metastasis. We establish that ECs are active and heterogeneous modulators of the TME, identifying specific therapeutic vulnerabilities within the tumor vasculature and providing a foundational blueprint for developing future precision immunotherapeutic strategies.